1997
DOI: 10.1111/j.1460-9568.1997.tb01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Figure‐Ground Segregation at Contours: a Neural Mechanism in the Visual Cortex of the Alert Monkey

Abstract: An important task of vision is the segregation of figure and ground in situations of spatial occlusion. Psychophysical evidence suggests that the depth order at contours is defined early in visual processing. We have analysed this process in the visual cortex of the alert monkey. The animals were trained on a visual fixation task which reinforced foveal viewing. During periods of active visual fixation, we recorded the responses of single neurons in striate and prestriate cortex (areas V1, V2, and V3/V3A). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…Thus, V2 neurons seem to depend on retinal disparity as has been reported for V1 neurons (Cumming & Parker, 2000), but in addition, include a mechanism for defining illusory contours and the direction of figure and ground at these contours. This agrees with earlier studies on illusory contours not requiring stereoscopic cues (Baumann, van der Zwan, & Peterhans, 1997), which showed that V2 neurons can be selective for certain figure -ground directions at these contours. Recently, comparable properties have been found for V2 neurons that signaled contours from random-dot stereograms (von der Heydt, , and in relation to overlapping squares or rectangles defined by luminance contrast .…”
Section: Comparison With Other Types Of Illusory Contour Stimulisupporting
confidence: 89%
“…Thus, V2 neurons seem to depend on retinal disparity as has been reported for V1 neurons (Cumming & Parker, 2000), but in addition, include a mechanism for defining illusory contours and the direction of figure and ground at these contours. This agrees with earlier studies on illusory contours not requiring stereoscopic cues (Baumann, van der Zwan, & Peterhans, 1997), which showed that V2 neurons can be selective for certain figure -ground directions at these contours. Recently, comparable properties have been found for V2 neurons that signaled contours from random-dot stereograms (von der Heydt, , and in relation to overlapping squares or rectangles defined by luminance contrast .…”
Section: Comparison With Other Types Of Illusory Contour Stimulisupporting
confidence: 89%
“…Subsequent studies have observed small fractions of V1 neurons selective for illusory contours, however. In some of these studies, it could be argued that luminance cues were present in some of the stimuli used (17,85), but in others that was not the case (150,243). Alternative explanations might relate to laminar positions in V1 (150), since end-stopped neurons are more frequent in superficial layers (98).…”
Section: Illusory Contours (Anomalous or Subjective Contours)mentioning
confidence: 96%
“…Displays that produce the perception of illusory contours can also evoke responses when the actual stimulation is confined to areas outside the classical receptive field (von der Heydt et al, 1984;Peterhans and von der Heydt, 1989). These responses might be related to figure-ground mechanisms (von der Heydt et al, 1993;Baumann et al, 1997;Heitger et al, 1998).…”
Section: Abstract: Primate Visual Cortex; Visual Perception; Perceptmentioning
confidence: 99%